La capacidad comunicante del espacio (2009)
This article works on the relationship between the space and the observer or participant of that space among them that makes place or communicational node that, when generating a similar effect among many people, consolidates the notion of the imaginary. This communication can be studied from the traditional pattern that proposes an issuing space for a receptor or from the current network type model that lead to the generation of the imaginary. Before the space we believe there is an architecture of words with which knit the sense of the experience, the words link ourselves with the territory in a specific way. Our experience transforms it into oral or written text or an audiovisual language. The space acquires sense because we speak and they speak to each other about it in literature, cinema, music, cultural industries, in the infinite stories that are built around it. Starting from discourse one lives the city